PLACEBO-CONTROLLED SUBJECTIVE AND OBJECTIVE EVALUATION OF LASER ANALGESIA EFFICACY - A CASE REPORT - Elitsa Veneva; Ani Belcheva (Peytchinski Publishing, 2019)
BACKGROUND: Pre-emptive laser analgesia (LA) is considered as bio-photomodulation of pulpal reactivity aiming reduction of nociceptive impulse formation and thus presenting a current non-pharmacological mean for painless conservative treatment. The aim of this investigation is efficacy approbation of a modified protocol for LA with Er:YAG laser. CASE DESCRIPTION: A 12 y.o. the female patient underwent two single-visit treatments, receiving LA and placebo analgesia (PA) prior to laser ablation of similar carious lesions in two permanent maxillary first molars bilaterally. Efficacy of analgesic protocol was assessed by following outcomes: primary - self-reported pain felt during treatment on VAS; secondary: changes in pulpal sensibility to electrical and cold-stimuli via EPT and Cold-test; pain-related behaviour on FLACC-scale; pulse frequency. Subjective and objective pain evaluation revealed no pain during caries ablation after LA and little pain after PA. Pulp sensibility towards electrical and thermal stimulation decreased more significantly after LA induction. DISCUSSION: Results suggest that Er:YAG therapy under applied parameters may be effective in achieving pulpal analgesia. The aforementioned tests could be valuable means for investigating the occurrence of any pulpal analgesic effect obtained by dental lasers. CONCLUSION: Assessment of the results of this case report should facilitate the development of a laser analgesia protocol. The clinical adequacy of the proposed protocol is to be separately estimated as part of a currently conducted double-blind randomized clinical trial with the split-mouth design.